39.5k views
2 votes
Answer the following question #2

Answer the following question #2-example-1
User MaNKuR
by
4.9k points

1 Answer

3 votes

9514 1404 393

Answer:

(2, 3)

Explanation:

The coefficients of x are opposites, so the x-terms can be eliminated by adding the two equations together:

(2x+3y) +(-2x+5y) = (13) +(11)

8y = 24 . . . simpify

y = 3 . . . . . divide by 8

Only one answer choice has y = 3: (x, y) = (2, 3).

__

If you like, you can finish the solution by substituting into one of the equations.

2x +3(3) = 13

2x = 4 . . . . . . . subtract 9

x = 2 . . . . . . . . divide by 2

The solution is (x, y) = (2, 3).

_____

A graph confirms this solution.

Answer the following question #2-example-1
User Stas Jaro
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.